Karakteristik Fisik dan Organoleptik Sereal Berbasis Kecambah Jagung-Kedelai - Bima Bayu; Siti Aminah; Nurhidajah - (Universitas Muhammadiyah Semarang, 2017)
The corn and soybean germination process were known to increase vitamin and mineral bioavailibility, there are not many food products were based on corn and soybean sprouts. The good nutrients content of corn and soybean sprouts potentially can be developed in to food products such as cereals. Cereals can be consumed as snack or food alternative. The general purpose of this research is to determine the effect of seedling corn and soybean sprouts formulation against physical and organoleptic characteristics of the corn-soybean sprouts cereals. The used research method is experiments using a randomized block design (RBD) monofaktorial with corn-soybean sprouts formula variation factor (control, 10:90, 30:70, 50:50, 70:30, 90:10, 100: 0). The physical (yield, kamba density, water absorbtion, and colour brightness) and organoleptic characteristics of product were analyzed, then thebest formulation results of both variable were proximate analyzed. The physical characteristics data were analyzed statistically by Anova follewed by a further test HSD while organoleptic test results were analyzed by the Wilcoxon and Friedmann test. The best result of the yield is 75,8% at 50:50, Kamba density of 0.03 g / ml in controls, water absorption of 3.7 ml / g at 50:50, and the brightness of 67.02 at 50:50. While the best organoleptic test results are cereals control. The summary result of the cornsoybean sprouts cereal with the variation on the corn-soybean sprouts formulation showed the real difference for each test performed where the best cereal formlation is 50:50.Keywords : Corn sprouts, soybean sprouts, Physical characteristics, Organoleptics, Cereal